An analysis of the rate of metallothionein mRNA poly(A)-shortening using RNA blot hybridization. - Mercer, J F (1985)
A progressive reduction in the size of rat metallothionein-1 mRNA following induction by copper chloride or dexamethasone was demonstrated on RNA blots, and was shown to be due to shortening of the poly(A)-tail. The rate of poly(A) removal was the same in rat liver and kidney following copper chloride induction, in rat liver following dexamethasone induction, and in mouse liver following copper chloride induction. In mouse liver metallothionein-1 and 2 mRNAs were shortened at the same rate. The reduction of the poly(A) tail was more rapid in the first 5 hours (approximately 20 nucleotides/h) but much slower (approximately 3 nucleotides/h) after the poly(A)-tail had been reduced to about 60 residues. Metallothionein mRNA molecules with poly(A) tail sizes less than 30-40 nucleotides were not observed. Exonuclease digestion of the poly(A)-tail is suggested, at least in the initial rapid phase. It is hypothesized that poly(A)-tails longer than 30 are required for mRNA stability and that much longer poly(A) tails may give newly synthesized mRNA molecules a competitive advantage in protein synthesis.